2010
DOI: 10.1523/jneurosci.5924-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cross Talk between Misfolded Proteins in Animal Models of Alzheimer's and Prion Diseases

Abstract: The central event in protein misfolding disorders (PMDs) is the accumulation of a misfolded form of a naturally expressed protein.Despite the diversity of clinical symptoms associated with different PMDs, many similarities in their mechanism suggest that distinct pathologies may cross talk at the molecular level. The main goal of this study was to analyze the interaction of the protein misfolding processes implicated in Alzheimer's and prion diseases. For this purpose, we inoculated prions in an Alzheimer's tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
149
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 51 publications
(63 reference statements)
4
149
2
1
Order By: Relevance
“…The presence of PrP enhances A␤ accumulation, and vice versa (15). Thus, in transgenic mice, the two proteins mutually accelerate the progression of both pathologies (16). In AD transgenic mice, the onset of prion disease symptoms developed at a rate proportional to the A␤ brain levels (16).…”
Section: Prion Protein (Prp)mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of PrP enhances A␤ accumulation, and vice versa (15). Thus, in transgenic mice, the two proteins mutually accelerate the progression of both pathologies (16). In AD transgenic mice, the onset of prion disease symptoms developed at a rate proportional to the A␤ brain levels (16).…”
Section: Prion Protein (Prp)mentioning
confidence: 99%
“…Thus, in transgenic mice, the two proteins mutually accelerate the progression of both pathologies (16). In AD transgenic mice, the onset of prion disease symptoms developed at a rate proportional to the A␤ brain levels (16). For humans, significant levels of A␤ deposition, similar to those found in AD patients, were seen in the brains of relatively young individuals who had died from Creutzfeldt-Jakob disease (17).…”
Section: Prion Protein (Prp)mentioning
confidence: 99%
“…86 Sc aggregates also seem to facilitate Aβ42 aggregation in vivo and AD mice developed a strikingly higher load of cerebral amyloid plaques that appeared much faster in prioninfected than in uninfected mice. 85 Our finding that Aβ42 binds to iPrP suggests that iPrP (the PrP Sc -like forms in uninfected human brains) may facilitate fibrillization of Aβ42 in AD (Fig. 1).…”
Section: Insoluble Prp C and Alzheimer Diseasementioning
confidence: 88%
“…[82][83][84] Although the exact biological relevance of the interaction between iPrP C and Aβ is unclear at present, it has been revealed that aggregation of one protein may facilitate aggregation of the other. 85 Synergistic interactions between other amyloidogenic proteins associated with neurodegeneration also have been reported to promote each other's fibrillization, amyloid deposition and formation of filamentous inclusions in transgenic mice. 86 Sc aggregates also seem to facilitate Aβ42 aggregation in vivo and AD mice developed a strikingly higher load of cerebral amyloid plaques that appeared much faster in prioninfected than in uninfected mice.…”
Section: Insoluble Prp C and Alzheimer Diseasementioning
confidence: 99%
“…Недавние исследования также показали, что процессы, связанные с неправильной укладкой одного из этих белков, являются серьезным фактором риска для индукции агрега-ции другого (Morales et al, 2010). На основании этих данных представля-ется перспективным изучение возможности взаимодействия и взаимного влияния агрегатов prp и aβ.…”
unclassified